The polarization of the south american integration: the Unasur case - Fenerick Júnior, José Bruno (2022)
This research seeks to answer the question: Why Argentina, Brazil, Chile, Colombia, Ecuador, Paraguay, Peru, and Uruguay left the Unasur, while Bolivia, Guyana, Surinam and Venezuela remained on the bloc? The hypothesis of this research is that ideology of domestic players, marked here by right-wing and left-wing spectrums, and its influence in the foreign policy decision-making explains the dismantlement of the Unasur. In order to answer the question presented, the research aims to map three domestic players involved in the foreign policy decision-making: the Executive, the Legislative and the Public Opinion (2008-2021). The methodology employed in this paper is based on specific literature about foreign policy decision-making and data collection of documents, diplomatic cables, legislative votes and surveys of public opinion available in the \"Las Americas y el Mundo\". Through Stata and R program, statistics models are also employed in order to identify the relation between ideology and the behavior of legislators and the public opinion towards Unasur. As results, it is possible to visualize an ideological polarization over the bloc in the Executive, the Legislative, and the Public Opinion, which gives empirical strength to corroborate to the idea that shifts in the ideology of the players in the domestic level were relevant to the dismantlement of the Unasur.